2019
DOI: 10.1002/ange.201907069
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Conflict as a Method to Create Stimuli‐Responsive Materials Based on Dynamic Helical Polymers

Abstract: A new multi‐sensor material based on helical copolymers showing the chiral conflict effect have been prepared. It can successfully detect and identify diverse metal cations in solution. The design of this material has taken into account not only the opposite helical senses induced by the two chiral monomers in the copolymer, but also their dynamic behavior. The induced helical sense can thus be enhanced, diminished, or inverted by interaction with different stimuli (that is, metal ions). Thus, depending on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…(b) Normalized water flux of the CT60/GO membrane during the alternate filtration of DI water and MB aqueous solution. (c) Comparison of water permeance and MB rejection for the CT60/GO membrane in this study with GO-based membranes reported in the literature. ,,, ,, Specific data on water permeance and MB rejection of reported GO-based membranes and other nanomaterial-based membranes can be found in Table S5.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…(b) Normalized water flux of the CT60/GO membrane during the alternate filtration of DI water and MB aqueous solution. (c) Comparison of water permeance and MB rejection for the CT60/GO membrane in this study with GO-based membranes reported in the literature. ,,, ,, Specific data on water permeance and MB rejection of reported GO-based membranes and other nanomaterial-based membranes can be found in Table S5.…”
Section: Resultsmentioning
confidence: 93%
“…The result indicated that the CT60/GO membrane has a stable separation performance. However, the XRD result indicated that the d -spacing of the membrane increased to 12.3 Å (Figure S10), which was potentially due to the invasion of dye molecules into the gap between GO nanosheets. , Figure c compares the CT60/GO membrane with prevailing GO-based membranes in terms of pure water permeance and MB selectivity. ,,, Moreover, the performance of the CT/GO membrane was also compared against membranes based on other nanomaterials, such as MXene and covalent organic frameworks (COFs), as shown in Table S5. The pure water permeance of the CT60/GO membrane was 171.5 L m –2 h –1 bar –1 and the MB rejection was 96.2%, suggesting the superior water permeance of the CT60/GO membrane and its application feasibility for dye separation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] This fact is related to the helical structure [20,21] adopted by the polymer-P or M helix, compressed/ stretched-, which can be tuned by the presence of external stimuli, and to the functional groups present in the pendant that will be oriented in a certain position towards the helix. Thus, it is possible to do helix inversion, screw sense enhancement or stretching/compression of the helix through different mechanisms-supramolecular interactions, [22][23][24][25][26][27][28] solvent polarity, [29][30][31] sergeants and soldiers effect, [26,33] majority rules [26] or chiral-to chiral communication mechanisms [33][34][35] that follow a cooperative effect. These structural changes in dynamic helical polymers are usually triggered either by the conformational composition of a chiral pendant or by the establishment of a supramolecular interaction between achiral pendants and chiral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…α ‐helical proteins or double‐helical DNA, are good candidates of chiral building block for 2D chiral materials [15, 16] . The conjugated helical polymers, poly(phenylacetylene)s (PPAs) possessing unique adjustable helical conformation are particularly attractive [17, 18] . The backbones of PPAs take a cis‐cisoidal ( c‐c ) or cis‐transoidal ( c‐t ) helical conformation with tunable helicity like molecular springs, controlled by the switchable intramolecular hydrogen bonding [19] .…”
Section: Introductionmentioning
confidence: 99%